2007
DOI: 10.3354/meps337103
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, growth and meadow characteristics of the seagrass Posidonia sinuosa along a depth-related gradient of light availability

Abstract: Morphological and growth characteristics of the meadow-forming seagrass Posidonia sinuosa (Cambridge et Kuo), were measured along a depth-related gradient of light to infer its response to long-term differences in light availability. Morphometric measurements were carried out at 6 depths between 1.6 and 9.0 m in summer and winter at Cockburn Sound and summer only at Warnbro Sound in south-western Australia. The minimum light requirement for P. sinuosa of 8.5% sub-surface light was among the lower range reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 53 publications
3
56
1
1
Order By: Relevance
“…It is well established that accumulation of C org in sediments and soils is strongly affected by net primary production (Cao and Woodward, 1998;Serrano et al, 2014). The decline with depth of C org stocks, C org accumulation rates and seagrass-derived inputs into the sedimentary pool that we observed coincides with reduced seagrass abundance and production reported by Collier et al (2007). These authors reported 18-24-fold reductions from shallow (2 m) to deep (8 m) P. sinuosa meadows in shoot density (from 1435 to 80 shoots m −2 ), aboveground biomass (from 899 to 47 g DW m −2 ) and belowground biomass (from 1028 to 43 g DW m −2 ) on the same depth gradient.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…It is well established that accumulation of C org in sediments and soils is strongly affected by net primary production (Cao and Woodward, 1998;Serrano et al, 2014). The decline with depth of C org stocks, C org accumulation rates and seagrass-derived inputs into the sedimentary pool that we observed coincides with reduced seagrass abundance and production reported by Collier et al (2007). These authors reported 18-24-fold reductions from shallow (2 m) to deep (8 m) P. sinuosa meadows in shoot density (from 1435 to 80 shoots m −2 ), aboveground biomass (from 899 to 47 g DW m −2 ) and belowground biomass (from 1028 to 43 g DW m −2 ) on the same depth gradient.…”
Section: Discussionsupporting
confidence: 55%
“…Here we studied Posidonia sinuosa meadows across a depth gradient, aiming to highlight key biogeochemical factors affecting C org storage in seagrass soils that need to be accounted for when attempting to produce regional or global estimates of C org storage in seagrass meadows. Previous research at this site (Collier et al, 2007(Collier et al, , 2008 showed significant variation in plant biomass and productivity, water quality and sediment biogeochemistry parameters across this depth gradient. Bare sediments were also sampled and studied in order to determine the "background" C org stocks and fluxes in the absence of a seagrass meadow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated for A. tribulus intermediate values in thallus light absorption efficiency, metabolic rates and TMA, but photosynthetic production per individual was as high as that of the rhodolith, thanks to its ability to form one the largest light collectors at the organism/canopy level. For the quantification of the size of the light collector of the whole organism, we used a parameter, LAI, common in terrestrial plant ecology, but not so common in marine ecology, although it has been successfully applied for the characterization of seagrass habitats (Olesen et al, 2002;Enríquez and Pantoja-Reyes, 2005;Collier et al, 2007). Seagrass LAI can explain changes in the magnitude of leaf self-shading within seagrass beds (Enríquez and Pantoja-Reyes, 2005) and leaf photoprotection (Schubert et al, 2015).…”
Section: Growth-form-speciesmentioning
confidence: 99%
“…Wicks et al (2009) suggested that increases in Z. marina leaf width and shoot length paired with less root growth in sediments with high organic content introduced more shear stress on the plants in the hydrologic conditions present in Chincoteague Bay which may have caused the plants with more aboveground biomass to be ripped out of the sediment; however, they did not replicate these conditions within mesocosms (Wicks et al 2009). The increase in aboveground to belowground biomass ratios increases respiratory demand which increases light requirements (Collier et al 2007). In the future, it would be beneficial to perform mesocosm experiments in flumes or to pair mesocosm experiments with field experiments as in Wicks et al (2009) …”
Section: Stress Measurementsmentioning
confidence: 99%